ANALISIS KINERJA KEUANGAN BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL DALAM DUAL BANKING SYSTEM - Tedi Rustendi (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2019)
ABSTRACTThis study aims to determine the growth performance of assets, third party funds and financing/loan provided, as well as financial performance indicators including capital adequacy ratio, financing/loan to deposit ratio, non performing financing/loan, income growth, return on asset, and operating expences to operating revenue ratio, between state-owned sharia banks and state-owned commercial banks (conventional). Data from the two groups of state-owned banks are placed in a multiple case study design with a mixed methods approach. The analysis shows that state-owned sharia banks are able to balance out state-owned banks in terms of asset growth, growth in third party funds, and growth in financing provided, but state-owned sharia banks need to compensate by increasing operational efficiency, efforts to reduce non performing financing and optimize financing.Key words: owned-state bank; performance; growth ABSTRAKPenelitian ini bertujuan untuk mengetahui kinerja pertumbuhan aset, dana pihak ketiga dan pembiayaan/kredit yang diberikan, serta indikator kinerja keuangan meliputi CAR, FDR/ LDR, NPF/ NPL, pertumbuhan laba, ROA, dan BOPO, antara bank umum syariah BUMN dengan bank umum persero (konvensional). Data dari kedua kelompok bank milik pemerintah tersebut ditempatkan dalam desain multiple case study dengan pendekatan mixed methods. Hasil analisis menunjukkan bahwa bank umum syariah BUMN mampu mengimbangi bank umum persero dalam hal pertumbuhan aset, pertumbuhan dana pihak ketiga, dan pertumbuhan pembiayaan yang diberikan, tetapi bank umum syariah BUMN perlu mengimbanginya dengan peningkatan efisiensi operasi, upaya menekan pembiayaan bermasalah dan mengoptimalkan pembiayaan.Kata kunci: bank BUMN; kinerja; pertumbuhan